2012
DOI: 10.1155/2012/269878
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Soil pH on the Alkaloid Content ofLupinus angustifolius

Abstract: Field studies were conducted in growing seasons 2004, 2005, and 2010 to investigate the effect of different soil pH values on the alkaloid content in seeds ofLupinus angustifolius. Two-year experiments with eleven cultivars were carried out in acid soils with an average ofpH=5.8(Mecklenburg-Western Pomerania) and on calcareous soils with an average pH of 7.1 (Bavaria), respectively. In addition, in 2010, eight cultivars were grown in field experiments in soils with pH values varying betweenpH=5.3andpH=6.7. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Because the seed alkaloid content, beyond the genetic background, is strongly influenced by environmental factors, such as drought, temperature, fertilization, and/or soil pH [43][44][45][46], the statistical analyses concerning the total alkaloid contents were carried out using accessions gathered in the Polish Lupinus Genebank that originated from one field experiment. However, this collection did not include the rough-seeded L. digitatus or two no longer available species, L. princei and L. somaliensis.…”
Section: Discussionmentioning
confidence: 99%
“…Because the seed alkaloid content, beyond the genetic background, is strongly influenced by environmental factors, such as drought, temperature, fertilization, and/or soil pH [43][44][45][46], the statistical analyses concerning the total alkaloid contents were carried out using accessions gathered in the Polish Lupinus Genebank that originated from one field experiment. However, this collection did not include the rough-seeded L. digitatus or two no longer available species, L. princei and L. somaliensis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, considerable environmental impacts on seed quality and yield have been reported in several studies. Seed protein, alkaloids and yield of German narrow-leafed lupins are proved to be significantly influenced by temperature and soil pH (Jansen, 2008;Jansen et al, 2009Jansen et al, , 2010Jansen et al, , 2012. Bhardwaj et al (1998) reported also a significant impact of growing conditions on seed composition of L. albus in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Also in L. angustifolius this feature was conferred by recessive alleles. Moreover, it has turned out that it is dependent on environmental conditions, including pH (Jansen et al 2012). According to Boersma et al (2005), reduced alkaloid content in L. angustifolius is controlled by three alleles of different loci.…”
Section: Resultsmentioning
confidence: 99%